PERBANDINGAN PENGATURAN HUKUM PIDANA TERHADAP RECKLESSNESS DALAM TINDAK PIDANA LALU LINTAS ANTARA INDONESIA DAN NEGARA LAIN - Andriyanto Andriyanto; Eko Soponyono; Bambang Tri Bawono; Anies Mashdurohatun (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
The increasingly complex development of traffic conditions increases the risk of accidents caused by careless or reckless driver actions. Traffic crimes resulting from recklessness have different legal implications in each country, particularly regarding the elements of fault, the form of criminal liability, and the sanctions applied. This article aims to compare the criminal law regulations regarding recklessness in traffic crimes between Indonesia and several other countries, specifically to identify differences in concepts, legal application, and the effectiveness of law enforcement. The research method used is normative juridical with a comparative legal approach, through analysis. legislation, legal doctrine, and related court decisions. The results of the study show that Indonesia regulates reckless acts in traffic accidents through Law Number 22 of 2009 concerning Road Traffic and Transportation with a focus on the element of negligence resulting in injury or death, while several other countries such as the United Kingdom, the United States and Germany apply the concept of recklessness as a low-level intention (culpable risk taking) with heavier criminal sanctions and stricter legal proof. This comparison shows the need for reconstruction of criminal law policy in Indonesia to clarify the boundaries between negligence and recklessness and increase the deterrent effect in order to reduce the number of traffic accidents and provide more optimal legal protection for the community.